Interactive Decision Making for Multiobjective Fuzzy Random Linear Programming Problems Using Expectations and Coefficients of Variation - Yano, Hitoshi; Matsui, Kota; Furuhashi, Mikiya (Lecture notes in engineering and computer science, 2014)
In this paper, an interactive decision making method for multiobjective fuzzy random linear programming problems using expectations and coefficients of variation is proposed. In the proposed method, it is assumed that the decision maker intends to not only maximize the expected degrees of possibilities that the original objective functions attain the corresponding fuzzy goals, but also minimize coefficients of variation for such possibilities, and such fuzzy goals are quantified by eliciting the corresponding membership functions. Using the fuzzy decision, such two kinds of membership functions are integrated. In the integrated membership space, a satisfactory solution is obtained from among an EV-Pareto optimal solution set through the interaction with the decision maker.